Evaluasi Pemanfaatan E-Modul dalam Program PembaTIK untuk Meningkatkan Kompetensi Guru Berbasis TIK - Suhaepi, Epi; Haryanto (Jurnal Ilmiah Global Education, 2025)
This study aims to evaluate the utilization of e-modules in the PembaTIK Program to enhance teachers' competencies in Information and Communication Technology (ICT). The research employed a descriptive evaluative approach using a survey technique, involving 31 top participants from all provinces in Indonesia and two experts in educational technology. Data were collected through an online questionnaire assessing the media and material aspects of the e-modules. The results show that, regarding the media aspect, participants rated text readability at 70% as very good, image quality at 60% as very good, layout design at 68% as very good, and media usage at 66% as very good. For the material aspect, the module's usefulness was rated 66% as very good, curriculum alignment 75%, content accuracy 56%, and material presentation 66%. Expert evaluations reinforced these findings, with the media aspect achieving an average of 85% very good and the material aspect 84% very good. The impact of this research demonstrates that e-modules significantly strengthen teachers’ self-directed learning, enhance their ICT professionalism, and suggest improvements in visual media quality and content updates to remain aligned with modern educational developments.